Enhancing Secondary Education Viewing Skills Through Differentiated Mobile Learning: A Lesson Learned from Teachers’ Perspective - Widora, Intan; Armanda, Muhamad Laudy; Yulia, Yuyun; Manullang, Agatha Christiyanti (Journal of Languages and Language Teaching, 2025)
The proliferation of mobile learning has introduced a wide range of educational apps and flexible learning supports, extending education beyond traditional constraints of time and location. While mobile learning has proven effective for language acquisition, its potential extends into areas of digital engagement critical to modern education. Differentiated instruction, essential for personalized learning, can particularly benefit from mobile learning platforms, as demonstrated in this study’s focus on viewing skills, a component highlighted in Indonesia’s Independent Curriculum but less explored in research. This qualitative study reflects on English teachers' experiences using mobile learning to teach viewing skills to secondary students across Indonesia, utilizing interviews, focus groups, and digital artefacts to gather insights. Findings reveal that mobile learning facilitates differentiated instruction in viewing skills, fosters student motivation and critical thinking, enhances digital literacy, and requires teacher strategies to mitigate distractions. These results suggest that structured mobile learning integration can effectively promote differentiated learning across diverse skills, offering educators a flexible tool for skill-specific instruction.